The Female FTSE Board Report 2022: What works? - Vinnicombe, Susan; Tessaro, Michelle (Cranfield University, 2022)
There has been a continued increase in the number of women on corporate boards. The percentage of women on FTSE 100 boards is 40% and the parallel percentage for FTSE 250 boards is 39%, meaning that FTSE 100 boards have already met the target set by the Women Leaders Review for 2025 and FTSE 250 are on the cusp of meeting it. Overall, women hold 413 directorships across FTSE 100 boards - the increase in women coming primarily as usual from female Non -Executive Directorships (NEDs). The number of women in Executive Directorships (EDs) has increased marginally from 31 to 36. A similar pro昀椀le emerges for FTSE 250 companies where women hold 752 directorships, of which 705 are NED and only 47 are EDs. There has been no change in the number of women EDs for the past three years. As in previous years there continues to be a wide variance between the top and bottom companies, indicating the downside of voluntary targets over mandatory quotas.